The Effect of Sports Activities toward Emotional Intelligence of Junior High School Students - Nur Mahfuzah Agustin; Amung Ma’mun; Tite Juliantine (JUARA : Jurnal Olahraga, 2019)
The purpose of this study was to examine the effect of sports activities on EI. The research method uses experimental research methods with pretest-posttest control group design. Participants in this study were extracurricular studentS SMP NU Kaplongan NU consists of 20 students. The research instrument used an EI questionnaire. Data analysis using independent samples t-test. The results of the study state that the factors that influence behavior change are more advanced among junior high school students, one of which is EI and there is an influence of sports activities on EI.